Diplomatic Geography of Xi Jinping: What the Statistics of the Chinese Leader’s Foreign Visits Reveal - I. Y. Zuenko; A. S. Osokin (Vestnik MGIMO-Universiteta)
This article seeks to delineate the foreign policy priorities of the People's Republic of China (PRC) by analyzing the international visits of Chinese President Xi Jinping. It posits that the evolution of a state's foreign policy can be traced through the foreign engagements of its leaders. This is particularly pertinent for China, where presidential visits are historically significant. The article offers an overview of China's traditional diplomacy and the foreign policy activities of Xi Jinping's predecessors. It concludes that Xi Jinping continues to undertake foreign visits in alignment with the «openness» policy, similar to his predecessors. Through a detailed analysis of the frequency and destinations of Xi Jinping's international visits over his two terms, the authors present a periodization of his foreign policy priorities. A comparative analysis is conducted on the visit frequencies of Xi Jinping and his predecessor, Hu Jintao, with adjustments for the impact of the COVID-19 pandemic. With Xi Jinping's re-election for a third term in 2023, this study provides insights into the nature and priorities of China's foreign policy for his current term and potential developments in the ongoing five-year political cycle. The findings indicate that from 2018 to 2023, Xi Jinping increased his visits to Southeast Asian countries, particularly Indonesia and Vietnam, while maintaining a consistent focus on Russia and the United States, akin to the approach under Jiang Zemin. The enduring partnership with Russia, spanning over two decades, corroborates the assertion that Sino-Russian relations are at their strongest in the history of bilateral ties. Data for this study were sourced from the Ministry of Foreign Affairs of China, the Administration of the President of the Russian Federation, and materials from the Chinavitae and China Power research projects.